2000
DOI: 10.1177/000494410004400106
|View full text |Cite
|
Sign up to set email alerts
|

Gifted, Streamed and Mixed-Ability Programs for Gifted Students: Impact on Self-Concept, Motivation, and Achievement

Abstract: G ifted and talented (GAT) students in a new regional selective GAT program were compared with GAT students in mixed ability and streamed classes. Outcomes were academic and non-academic self-concepts, motivation orientations, and achievement tests administered at the start and end of the school year. Selective GAT students' gains were not significantly better than comparison GAT student's gains on any outcome. Selective GAT students' scores were significantly more negative for all facets of academic self-conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 33 publications
4
49
0
1
Order By: Relevance
“…Perhaps, with a gifted population, this same decline is evident. This decline in mastery orientation for gifted students grouped together in the present study was consistent with findings by other researchers (Craven, Marsh, & Print, 2000). However it must be noted that this research did not explore whether the gifted children were in fact challenged sufficiently or appropriately in these selective class groupings.…”
Section: Performance Goal Orientationsupporting
confidence: 92%
“…Perhaps, with a gifted population, this same decline is evident. This decline in mastery orientation for gifted students grouped together in the present study was consistent with findings by other researchers (Craven, Marsh, & Print, 2000). However it must be noted that this research did not explore whether the gifted children were in fact challenged sufficiently or appropriately in these selective class groupings.…”
Section: Performance Goal Orientationsupporting
confidence: 92%
“…An analysis in 26 countries found that students in selective schools with high average achievement tend to have lower academic self-concepts than students in non-selective schools (Marsh & Hau, 2003). Students also compare themselves with others in their class (Chapman & Tunmer, 1997;Craven, Marsh, & Print, 2000;Kulik & Kulik, 1982). In schools with streaming, where students are placed into classes according to ability and remain in those classes for most subjects, the class provides a stronger frame of reference than the school (Wong & Watkins, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies which took the achievement level of the peer reference group as a predictor of individual levels of test anxiety into account. A prominent theoretical approach referring to the effects of the achievement level of the peer reference group on individual experiences of self-concept is the ''big-fish-little-pond effect'' (BFLPE; Marsh, 1987) which has been repeatedly attested to in gifted student populations when comparing gifted students attending special gifted classes with those attending regular classes (e.g., Craven, Marsh, & Print, 2000;Marsh, Chessor, Craven, & Roche, 1995;Zeidner & Schleyer, 1999a).…”
mentioning
confidence: 99%